Treatment Options for Patients With Heavily Pretreated Relapsed and Refractory Multiple Myeloma - Dimopoulos, Meletios-Athanasios; Richardson, Paul; Lonial, Sagar (Clinical lymphoma, myeloma and leukemia, 2022)
Despite the increasing number of treatment options available for multiple myeloma, relapse is still inevitable and there remains a critical unmet need for treatments for patients with late-stage, highly refractory disease. In this review, we discuss currently approved treatment options for heavily pretreated patients with relapsed and refractory multiple myeloma, with a focus on the optimal management of patients with MM refractory to lenalidomide, bortezomib, and in some cases, daratumumab or an anti-CD38 monoclonal antibody. Data from recent clinical trials of immunomodulatory agents (pomalidomide), proteasome inhibitors (PIs; carfilzomib and ixazomib), monoclonal antibodies (elotuzumab, daratumumab, and isatuximab), and other novel therapies (including panobinostat-based therapy) are summarized. We also provide potential therapeutic strategies for patients according to different treatment histories, and include case studies to illustrate the practical use of various treatment options in a clinical setting. Regimens containing pomalidomide, elotuzumab, next-generation PIs, panobinostat, or selinexor may provide effective treatment options in patients with triple-refractory disease. The choice of agents used, and combinations thereof should be individualized as well as strategically planned from early- to late-stage relapse.